Optimization of Pr3+-doped glasses for photonic applications: an overview and challenges in Judd–Ofelt analysis - Kesavulu, C. R.; Soumya, S.; Saikia, Darshana; Jayasankar, Deviprasad Chalicheemalapalli; Pecharapa, Wisanu; Jayasankar, C. K. (My University, 2026)
Characteristics (optical, luminescence, up-conversion, etc.) of triply ionized Praseodymium (Pr3+) ions doped glasses, glass-ceramics, phosphors and crystals have been widely studied for the development of photonic devices. Most of these characteristics are mainly based on Judd–Ofelt (JO) theory to interpret transition intensities and in turn to simulate radiative properties of Pr3+ ions based optical materials. However, JO analysis provides inconsistent results for Pr3+:glasses. Further, besides no review is available focusing on uneven findings of Pr3+:glasses. Therefore, a comprehensive data on Pr3+:glasses have been collected (490 Pr3+:glasses) and compared, besides labeling glass compositions systematically. The properties that are reviewed include, Nephelauxetic effect, optical energy gap, thermal, JO parameters, radiative properties, etc. It has been noticed that the systematic study either in preparation or optimization of characteristic properties are very much missing. Moreover, large number of data sets of literature are presented at one place which is very much useful for predictive modeling approaches. Also, the primary focus of the present review is not to provide a comprehensive summary of all studies conducted so far or to discuss new findings, but rather to highlight the challenges associated with JO parameters for Pr3+ ions that influence the development of optical materials, components, and applications.
Keywords: Judd–Ofelt analysis; optical properties; photonic applications; Pr3+-doped glasses